Method for passivating high-entropy alloy through gas

By ball milling in the air and passing into N2:Xvol.%O2 mixed gas for gas passivation, the problem of easy spontaneous combustion and high cost of preparation of high entropy alloy powder is solved, and the high entropy alloy powder is easily and safely prepared in the air, reducing production costs.

CN119753400APending Publication Date: 2025-04-04YANSHAN UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510037327.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The preparation of existing high entropy alloy powders is prone to spontaneous combustion and has high preparation costs, making it difficult to complete the preparation in air.

Method used

High entropy alloy powder is prepared by ball milling in air, and gas passivation is carried out through a ball milling tank for N2:Xvol.%O2 mixture gas, which simplifies the preparation process and takes materials in the air to produce high entropy alloy powder.

Benefits of technology

It realizes the easy preparation of high-entropy alloy powder in the air, reduces production costs and avoids the risk of spontaneous combustion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a method for passivating a high-entropy alloy through gas. The method comprises the following steps that S1, high-entropy alloy powder is prepared; s2, sintering preparation of high-entropy alloy powder; wherein inert gas or N2: X vol.% O2 (x = 0-30) gas is introduced into a ball milling tank, gas introduction is repeated for 0-5 times, standing is performed for 0-5 h, and then material taking is performed in air, or inert gas or N2: X vol.% O2 (x = 0-30) gas is introduced in the middle section of ball milling for 10-25 h, ball milling continues to be performed for 10-25 h, standing is performed for 0-5 h, material taking is performed in air, high-entropy alloy powder with the fineness of 150 nm is prepared, and then sintering is performed. According to the method, the high-entropy alloy can be prepared without being carried out in a vacuum or Ar gas environment by changing a ball milling process, so that the process is greatly simplified, the preparation process is simple, and the cost of preparing the high-entropy alloy is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal materials, and in particular relates to a method for gas passivation of high entropy alloys. Background Art

[0002] At present, the most widely used method for preparing high entropy alloys in industry is the melt-casting method. However, the melt-casting method not only requires that the melting points of the main elements are not much different, but also it is difficult to avoid segregation and uneven composition during the process of liquid to solid transformation. In addition, it needs to be prepared under inert gas or vacuum environment. In contrast, the high entropy alloy prepared by MA method can greatly improve the mutual solubility between elements, which is more conducive to the formation of high entropy solid solution and can produce nano-scale high entropy alloy powder. [Qi Peibu, Liang Xiubing, Tong Yonggang, et al. Effect of ball milling time on mechanical alloying preparation of NbMoTaW high entropy alloy powder[J]. Rare Metal Materials and Engineering, 2019, 48(08): 2623-2629.] The effect of ball milling time on the preparation of NbMoTaW high entropy alloy by MA method was studied. It was found that the alloying degree of powder was related to the surface morphology of particles. The more severe the surface deformation, the higher the alloying degree. For the preparation of NbMoTaW high entropy alloy, ball milling for 45h is the best, and the prepared powder has a simple structure and uniform composition. However, since the powder will generate very high internal energy and surface energy after MA, if the material is taken directly in the air, the powder is very likely to spontaneously combust, causing danger. Therefore, it needs to be prepared in a specific inert gas atmosphere. The preparation process is relatively cumbersome and not suitable for application in industrial production. Therefore, it is necessary to develop a method for passivating high entropy alloys, simplify the preparation process on the basis of ensuring performance, so that it can be prepared in the air and reduce production costs. Summary of the invention

[0003] In view of this, the technical problem to be solved by the present invention is to provide a method for gas passivation of high entropy alloys, which solves the problem of easy spontaneous combustion and high preparation cost of high entropy alloy powder in the prior art.

[0004] In order to solve the above technical problems, the present invention discloses a method for gas passivation of high entropy alloy, which is characterized by comprising the following steps: S1, preparation of high entropy alloy powder; S2, preparation of high entropy alloy powder by sintering; Among them, S1, high entropy alloy powder preparation: the metal single substance component powder with a purity of >99% is weighed and mixed in the air according to a predetermined ratio and loaded into a stainless steel tank, the ball-to-material mass ratio is 10:1-20:1, the rotation speed is 300-600r / min, the machine is stopped for 2 hours for heat dissipation every 5 hours, the ball milling time is 20-50 hours, and after the ball milling is completed, it is allowed to stand for 0-10 hours, and then N2:Xvol.%O2 mixed gas is introduced into the ball mill tank, and the ventilation is repeated for 0-5 times. After standing for 0-5 hours, the material is taken out in the air to obtain a high entropy alloy powder with a diameter of 150nm or finer.

[0005] S2, high entropy alloy powder sintering preparation: The high entropy alloy powder after gas passivation in S1 was pre-pressed and loaded into a graphite mold, and spark plasma sintering was performed using a LABOXTM-110 spark plasma sintering instrument. First, the vacuum degree was evacuated to 40 Pa; then, the set sintering pressure was slowly applied to the sample; then, it was heated from room temperature to 600°C in 5 minutes, and kept at 600°C for 10 minutes. In the last minute of the insulation, the vacuum button was turned off, the argon valve was opened, and argon was filled to -0.05 Pa, and the temperature was increased from 600°C to 900°C at a heating rate of 50°C / min, and then from 900°C to 950°C at a heating rate of 25°C / min, and kept at 950°C for 10 minutes. Finally, it was cooled with the furnace to obtain a blank, and the prepared blank was subjected to surface grinding and deburring to obtain a high entropy alloy.

[0006] Furthermore, the above-mentioned S1, high entropy alloy powder preparation: the metal single substance component powder with a purity of> 99% is weighed and mixed in a stainless steel tank according to a predetermined ratio in the air, the ball-to-material mass ratio is 10:1-20:1, the rotation speed is 300-600r / min, the machine is stopped for 2 hours for heat dissipation every 5 hours, the ball milling time is 20-50h, and N2:X vol.%O2 mixed gas is introduced for 10-25h in the middle of the ball milling, and the ball milling is continued for 10-25h. After standing for 0-5h, the material is taken out of the air to obtain a high entropy alloy powder with a diameter of 150nm or finer.

[0007] Furthermore, in the above N2:X vol.%O2 mixed gas, X=0-30 vol.%.

[0008] Compared with the prior art, the present application can obtain the following technical effects: The present invention changes the ball milling process so that the high entropy alloy can be prepared without vacuum or Ar gas environment, which greatly simplifies the process, makes the preparation process simple, and reduces the cost of preparing the high entropy alloy.

[0009] Of course, any product implementing this application does not necessarily need to achieve all of the technical effects described above at the same time. DETAILED DESCRIPTION

[0010] The following will explain the implementation methods of the present application in detail with reference to examples, so that the implementation process of how the present application uses technical means to solve technical problems and achieve technical effects can be fully understood and implemented accordingly. Example 1

[0011] The CoCrNiCuFe high entropy alloy raw materials were weighed in the air according to the given ratio in Table 1 and mixed into a stainless steel tank. The ball-to-material mass ratio was 10:1. The rotation speed was 300 r / min. The machine was stopped for 2 h for heat dissipation after every 5 h of rotation. After the ball milling time was 15 h, Ar was introduced into the ball milling tank and the ball milling was continued for 15 h. After standing for 2 h, the material was taken out in the air to obtain CoCrNiCuFe high entropy alloy powder with a particle size of 150 nm or more.

[0012]

[0013] The gas-passivated CoCrNiCuFe high entropy alloy powder was pre-pressed and loaded into a graphite mold. The spark plasma sintering was carried out using a LABOXTM-110 spark plasma sintering apparatus. First, the vacuum degree was evacuated to 40 Pa. Then, the set sintering pressure was slowly applied to the sample. Then, it was heated from room temperature to 600 °C in 5 min, and kept at 600 °C for 10 min. In the last minute of the insulation, the vacuum button was turned off, the argon valve was opened, and argon was filled to -0.05 Pa. The temperature was increased from 600 °C to 900 °C at a heating rate of 50 °C / min, and then from 900 °C to 950 °C at a heating rate of 25 °C / min, and kept at 950 °C for 10 min. Finally, it was cooled in the furnace to obtain a blank. The prepared blank was subjected to surface grinding and deburring to obtain a CoCrNiCuFe high entropy alloy.

[0014] The prepared CoCrNiCuFe high entropy alloy was polished and then tested for structure and performance using instruments used in conventional testing methods. The obtained technical parameters are as follows: Example 2

[0015] The CoCrNiCuFe high entropy alloy raw materials were weighed in the air according to the given ratio in Table 1 and mixed into a stainless steel tank. The ball-to-material mass ratio was 10:1. The rotation speed was 300 r / min. The machine was stopped for 2 h for heat dissipation after every 5 h of rotation. After the ball milling time was 30 h, Ar was introduced into the ball milling tank. The machine was milled at 250 r / min for 5 min and then Ar was introduced. The machine was milled at 200 r / min for 3 min and then Ar was introduced. After standing for 2 h, the material was taken out in the air to obtain CoCrNiCuFe high entropy alloy powder with a particle size of 150 nm or more.

[0016] The gas-passivated CoCrNiCuFe high entropy alloy powder was pre-pressed and loaded into a graphite mold. The spark plasma sintering was carried out using a LABOXTM-110 spark plasma sintering apparatus. First, the vacuum degree was evacuated to 40 Pa. Then, the set sintering pressure was slowly applied to the sample. Then, it was heated from room temperature to 600 °C in 5 min, and kept at 600 °C for 10 min. In the last minute of the insulation, the vacuum button was turned off, the argon valve was opened, and argon was filled to -0.05 Pa. The temperature was increased from 600 °C to 900 °C at a heating rate of 50 °C / min, and then from 900 °C to 950 °C at a heating rate of 25 °C / min, and kept at 950 °C for 10 min. Finally, it was cooled in the furnace to obtain a blank. The prepared blank was subjected to surface grinding and deburring to obtain a CoCrNiCuFe high entropy alloy.

[0017] The prepared CoCrNiCuFe high entropy alloy was polished and then tested for structure and performance using instruments used in conventional testing methods. The obtained technical parameters are as follows: Example 3

[0018] The CoCrNiCuFe high entropy alloy raw materials were weighed in the air according to the given ratio in Table 1 and mixed into a stainless steel tank. The ball-to-material mass ratio was 10:1. The rotation speed was 300 r / min. The mill was stopped for 2 h for heat dissipation after every 5 h of milling. After the ball milling time was 30 h, Ar was introduced into the ball mill. After standing for 2 h, the material was taken out in the air to obtain CoCrNiCuFe high entropy alloy powder with a particle size of 150 nm or more.

[0019] The gas-passivated CoCrNiCuFe high entropy alloy powder was pre-pressed and loaded into a graphite mold. The spark plasma sintering was carried out using a LABOXTM-110 spark plasma sintering apparatus. First, the vacuum degree was evacuated to 40 Pa. Then, the set sintering pressure was slowly applied to the sample. Then, it was heated from room temperature to 600 °C in 5 min, and kept at 600 °C for 10 min. In the last minute of the insulation, the vacuum button was turned off, the argon valve was opened, and argon was filled to -0.05 Pa. The temperature was increased from 600 °C to 900 °C at a heating rate of 50 °C / min, and then from 900 °C to 950 °C at a heating rate of 25 °C / min, and kept at 950 °C for 10 min. Finally, it was cooled in the furnace to obtain a blank. The prepared blank was subjected to surface grinding and deburring to obtain a CoCrNiCuFe high entropy alloy.

[0020] The prepared CoCrNiCuFe high entropy alloy was polished and then tested for structure and performance using instruments used in conventional testing methods. The obtained technical parameters are as follows: Example 4

[0021] The CoCrNiCuFe high entropy alloy raw materials were weighed in the air according to the given ratio in Table 1 and mixed into a stainless steel tank. The ball-to-material mass ratio was 10:1. The rotation speed was 300 r / min. The mill was stopped for 2 h after every 5 h of rotation to dissipate heat. After the ball milling time was 30 h, N2:5 vol.% O2 was introduced into the ball mill. After standing for 2 h, the material was taken out in the air to obtain CoCrNiCuFe high entropy alloy powder with a particle size of 150 nm or more.

[0022] The gas-passivated CoCrNiCuFe high entropy alloy powder was pre-pressed and loaded into a graphite mold. The spark plasma sintering was carried out using a LABOXTM-110 spark plasma sintering apparatus. First, the vacuum degree was evacuated to 40 Pa. Then, the set sintering pressure was slowly applied to the sample. Then, it was heated from room temperature to 600 °C in 5 min, and kept at 600 °C for 10 min. In the last minute of the insulation, the vacuum button was turned off, the argon valve was opened, and argon was filled to -0.05 Pa. The temperature was increased from 600 °C to 900 °C at a heating rate of 50 °C / min, and then from 900 °C to 950 °C at a heating rate of 25 °C / min, and kept at 950 °C for 10 min. Finally, it was cooled in the furnace to obtain a blank. The prepared blank was subjected to surface grinding and deburring to obtain a CoCrNiCuFe high entropy alloy.

[0023] The prepared CoCrNiCuFe high entropy alloy was polished and then tested for structure and performance using instruments used in conventional testing methods. The obtained technical parameters are as follows: Example 5

[0024] The CoCrNiCuFe high entropy alloy raw materials were weighed in the air according to the given ratio in Table 1 and mixed into a stainless steel tank. The ball-to-material mass ratio was 10:1. The rotation speed was 300 r / min. The mill was stopped for 2 h for heat dissipation after every 5 h of rotation. After the ball milling time was 30 h, N2 was introduced into the ball mill. After standing for 2 h, the material was taken out in the air to obtain CoCrNiCuFe high entropy alloy powder with a particle size of 150 nm or more.

[0025] The gas-passivated CoCrNiCuFe high entropy alloy powder was pre-pressed and loaded into a graphite mold. The LABOXTM-110 spark plasma sintering instrument was used for spark plasma sintering. First, the vacuum degree was evacuated to 40 Pa. Then, the set sintering pressure was slowly applied to the sample. Then, it was heated from room temperature to 600℃ in 5 minutes, and kept at 600℃ for 10 minutes. In the last minute of the insulation, the vacuum button was turned off, the argon valve was opened, and argon was filled to -0.05 Pa. The temperature was increased from 600℃ to 900℃ at a heating rate of 50℃ / min, and then from 900℃ to 950℃ at a heating rate of 25℃ / min, and kept at 950℃ for 10 minutes. Finally, it was cooled in the furnace to obtain a blank. The prepared blank was subjected to surface grinding and deburring to obtain a CoCrNiCuFe high entropy alloy.

[0026] The prepared CoCrNiCuFe high entropy alloy was polished and then tested for structure and performance using instruments used in conventional testing methods. The obtained technical parameters are as follows: Example 6

[0027] The CoNiCuFeMn high entropy alloy raw materials were weighed in the air according to the given ratio in Table 7 and mixed into a stainless steel tank. The ball-to-material mass ratio was 10:1. The rotation speed was 300 r / min. The machine was stopped for 2 h for heat dissipation after every 5 h of rotation. After the ball milling time was 15 h, Ar was introduced into the ball milling tank and the ball milling was continued for 15 h. After standing for 2 h, the material was taken out in the air to obtain CoNiCuFeMn high entropy alloy powder with a particle size of 150 nm or more.

[0028]

[0029] The gas-passivated CoNiCuFeMn high entropy alloy powder was pre-pressed and loaded into a graphite mold. The sample was subjected to spark plasma sintering using a LABOXTM-110 spark plasma sintering apparatus. First, the vacuum was evacuated to 40 Pa. Then, the set sintering pressure was slowly applied to the sample. Next, the sample was heated from room temperature to 600 °C in 5 min and kept at 600 °C for 10 min. In the last minute of the heat preservation, the vacuum button was turned off, the argon valve was opened, and the argon gas was filled to -0.05 Pa. The temperature was raised from 600 °C to 1000 °C at a heating rate of 50 °C / min, and then from 1000 °C to 1050 °C at a heating rate of 25 °C / min, and kept at 1050 °C for 10 min. Finally, the sample was cooled in the furnace to obtain a blank. The blank was subjected to surface grinding and deburring to obtain a CoNiCuFeMn high entropy alloy.

[0030] The prepared CoNiCuFeMn high entropy alloy was polished and then tested for structure and performance using instruments used in conventional testing methods. The obtained technical parameters are as follows: Example 7

[0031] The CoNiCuFeMn high entropy alloy raw materials were weighed in the air according to the given ratio in Table 7 and mixed into a stainless steel tank. The ball-to-material mass ratio was 10:1. The rotation speed was 300 r / min. The mill was stopped for 2 h for every 5 h of rotation to dissipate heat. After the ball milling time was 30 h, N2 was introduced into the ball mill. After standing for 2 h, the material was taken out in the air to obtain CoNiCuFeMn high entropy alloy powder with a particle size of 150 nm or more.

[0032] The gas-passivated CoNiCuFeMn high entropy alloy powder was pre-pressed and loaded into a graphite mold. The sample was subjected to spark plasma sintering using a LABOXTM-110 spark plasma sintering apparatus. First, the vacuum was evacuated to 40 Pa. Then, the set sintering pressure was slowly applied to the sample. Next, the sample was heated from room temperature to 600 °C in 5 min and kept at 600 °C for 10 min. In the last minute of the heat preservation, the vacuum button was turned off, the argon valve was opened, and the argon gas was filled to -0.05 Pa. The temperature was raised from 600 °C to 1000 °C at a heating rate of 50 °C / min, and then from 1000 °C to 1050 °C at a heating rate of 25 °C / min, and kept at 1050 °C for 10 min. Finally, the sample was cooled in the furnace to obtain a blank. The blank was subjected to surface grinding and deburring to obtain a CoNiCuFeMn high entropy alloy.

[0033] The prepared CoNiCuFeMn high entropy alloy was polished and then tested for structure and performance using instruments used in conventional testing methods. The obtained technical parameters are as follows:

[0034] In summary, the present invention changes the ball milling process so that the high entropy alloy can be prepared without vacuum or Ar gas environment, which greatly simplifies the process, makes the preparation process simple, and reduces the cost of preparing the high entropy alloy.

[0035] The above description shows and describes several preferred embodiments of the present invention, but as mentioned above, it should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the invention concept described herein through the above teachings or the technology or knowledge of the relevant field. Changes and variations made by those skilled in the art do not depart from the spirit and scope of the present invention, and should be within the scope of protection of the claims attached to the present invention.

Claims

1. A method for gas passivation of high entropy alloys, characterized in that: The steps include: S1, preparation of high entropy alloy powder; S2, preparation of high entropy alloy powder by sintering; Among them, S1, high entropy alloy powder preparation: the metal single substance component powder with a purity of >99% is weighed and mixed in a stainless steel tank according to a predetermined ratio in the air, the ball-to-material mass ratio is 10:1-20:1, the rotation speed is 300-600 r / min, the machine is stopped for 2 hours for heat dissipation every 5 hours, the ball milling time is 20-50 hours, after the ball milling is completed, it is allowed to stand for 0-10 hours, and then N2:X vol.%O2 mixed gas is introduced into the ball milling tank, and the ventilation is repeated for 0-5 times. After standing for 0-5 hours, the material is taken out in the air to obtain a high entropy alloy powder with a fineness of 150nm; S2, high entropy alloy powder sintering preparation: The high entropy alloy powder after gas passivation in S1 was pre-pressed and loaded into a graphite mold, and the LABOXTM-110 spark plasma sintering instrument was used for spark plasma sintering. First, the vacuum degree was evacuated to 40Pa; then, the set sintering pressure was slowly applied to the sample; then, it was heated from room temperature to 600℃ in 5min, and kept at 600℃ for 10min. In the last minute of the insulation, the vacuum button was turned off, the argon valve was opened, and argon was filled to -0.05 Pa, and the temperature was increased from 600℃ to 900℃ at a heating rate of 50℃ / min, and then from 900℃ to 950℃ at a heating rate of 25℃ / min, and kept at 950℃ for 10min. Finally, it was cooled with the furnace to obtain a blank, and the prepared blank was subjected to surface grinding and deburring to obtain a high entropy alloy.

2. The method for gas passivation of high entropy alloy according to claim 1, characterized in that: S1, preparation of high entropy alloy powder: weigh and mix metal single substance component powder with a purity of >99% in air according to a predetermined ratio and put it into a stainless steel tank, the ball-to-material mass ratio is 10:1-20:1, the rotation speed is 300-600 r / min, the machine is stopped for 2 hours for heat dissipation every 5 hours, the ball milling time is 20-50 hours, and N2:X vol.%O2 mixed gas is introduced for 10-25 hours in the middle of the ball milling, and the ball milling is continued for 10-25 hours. After standing for 0-5 hours, the material is taken out of the air to obtain a high entropy alloy powder with a fineness of 150nm or more.

3. The method for gas passivation of high entropy alloy according to any one of claims 1 and 2, characterized in that: In the N2:Xvol.%O2 mixed gas, X=0-30 vol.%.

Citation Information

Cited By

  • High-entropy alloy preparation process parameter regulation and control method and system

    CN121373435A